DBD‐based plasma polymerization from monomer‐argon mixtures: Analytical model of monomer reactions with excited argon species. Issue 12 (19th July 2017) - Klages, Claus‐Peter; Czerny, Andreas K.; Philipp, Jens; Becker, Markus M.; Loffhagen, Detlef
Abstract : Experimental studies of DBD‐based atmospheric‐pressure plasma polymerization from mixtures of hexamethyldisiloxane (HMDSO) with argon are presented and interpreted using an analytical model of the plasma‐chemical kinetics. Gradient films are obtained using a special DBD‐PACVD reactor. Growth‐rate profiles and their monomer fraction dependence show that long‐living excited Ar species play a major role in the deposition mechanism. Reactions of HMDSO with metastable and resonance argon atoms as well as argon excimers are considered within the presented model which may be simplified by introducing a lumped excited argon species Ar*. Model predictions are compared with experimental results. Recombination reactions must be included in order to reproduce characteristic features of the measured growth‐rate curves. Abstract : A kinetic model of DBD‐based plasma polymerization from Ar/HMDSO is outlined, involving six excited Ar species. A system of algebraic equations between T‐averaged particle densities of excited Ar species is derived and solved recursively, T being half an ac period. Growth‐rate profiles are calculated using a simplified chemical model. Inclusion of recombination reactions with plausible rate constants results in a good agreement with experimental growth‐rate data.